2015
DOI: 10.1002/jocb.122
|View full text |Cite
|
Sign up to set email alerts
|

Re-Operationalizing Established Groups in Brainstorming: Validating Osborn's Claims

Abstract: Since the introduction of brainstorming as an idea‐generation technique to address organizational problems, researchers have struggled to replicate some of the claims around the technique. One major concern has been the differences in the number of ideas generated between established groups as found in industry versus the non‐established groups used in the laboratory. The impact of group establishment on idea quality has also been an area of interest. This study addresses these issues by using a more in‐depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Since its initial conceptualization, research has been conducted on different approaches to brainstorming. Levine, Heuett, and Reno (2015) found that well-established groups, similar to those found in organizations, generated more ideas, as well as ideas of higher quality, when compared to workgroups that were not well-established. There is debate around whether group brainstorming is best conducted outright or after individual members have had the opportunity to brainstorm on their own.…”
Section: Resultsmentioning
confidence: 81%
“…Since its initial conceptualization, research has been conducted on different approaches to brainstorming. Levine, Heuett, and Reno (2015) found that well-established groups, similar to those found in organizations, generated more ideas, as well as ideas of higher quality, when compared to workgroups that were not well-established. There is debate around whether group brainstorming is best conducted outright or after individual members have had the opportunity to brainstorm on their own.…”
Section: Resultsmentioning
confidence: 81%
“…Design ideas that are product of combinations and development of other ideas tend to be of superior quality (Linsey, Clauss et al, 2011), which supports the role of combinatorial processes to transform "mediocre ideas into sterling ideas" (Osborn, 1963, p. 158). • One of the few studies that compared established (worked together for 10 weeks) vs. non-established groups (only worked together once for the brainstorm session) found evidence that validates Osborn's claims (Levine, Heuett et al, 2017).…”
Section: A Health Check-up Of An Octogenarianmentioning
confidence: 69%
“…Design ideas that are product of combinations and development of other ideas tend to be of superior quality (Linsey, Clauss et al, 2011), which supports the role of combinatorial processes to transform "mediocre ideas into sterling ideas" (p. 158). • One of the few studies that compared established (worked together for 10 weeks) vs. nonestablished groups (only worked together once for the brainstorm session) confirms Osborn's claims about increased group efficiency (Levine, Heuett et al, 2017). • Evidence confirms that "idea-spurring questions" can have positive effects in creative ideation (Moreno and Yang, 2014).…”
Section: The First Decade Of Studiesmentioning
confidence: 77%